'By Fraud and Collusion': Feudal Revenue and Enforcement of the Statute of Marlborough, 1267–1526. Issue 1 (2nd January 2021) - Hannay, Ashley
ABSTRACT: Following the Statute of Marlborough 1267, feoffments which were designed to deprive lords of wardship could in some circumstances be deemed 'collusive' or 'fraudulent'. This was further complicated from the mid-fourteenth century onwards by the common practice of creating uses to circumvent the common law rules prohibiting the devise of land by last will. The effect of uses being created to perform last wills was that lords, in particular the king, were losing out on their feudal incidents. The current view, put forward by legal historians, is that the Crown struggled to enforce the Statute of Marlborough after 1410, and that the 'campaign' against this loss of feudal revenue began in the 1520s. This article seeks to re-examine this view, particularly in relation to how Marlborough and collusion were understood and the Crown's approach to the avoidance of feudal incidents before the Statute of Uses 1536.